Phenotypic and genetic characterization of Pseudomonas syringae strains associated with the recent citrus bacterial blast and bacterial black pit epidemics in Tunisia. (16th January 2017) - Abdellatif, E.; Kałużna, M.; Janse, J. D.; Sobiczewski, P.; Helali, F.; Lamichhane, J. R.; Rhouma, A.
Abstract : In the spring of 2012, symptoms of a disease resembling citrus blast and citrus black pit were observed in some orchards in Tunisia. The epidemic spread rapidly in the following years. Twenty‐four commercial citrus orchards from four Tunisian regions showing characteristic symptoms of bacterial diseases were surveyed during a 3‐year study. Eighty‐eight Pseudomonas‐ like bacterial isolates were successfully obtained from the northeast and west of Tunisia. No isolates were recovered from the central region. Overall, 46 isolates were identified as Pseudomonas syringae pv. syringae and most of them showed similar phenotypic and genetic profiles. The virulence of three selected isolates differed from one plant cultivar to another as well as from the type of plant organ used for the inoculation. In a bioassay test, all isolates produced syringomycin, which was confirmed by molecular detection based on the syrB and syrD genes. Only EC122 possessed syrD but not syrB . DNA fingerprints, based on repetitive sequence‐based polymerase chain reaction (rep‐PCR) and PCR melting profile (PCR MP), were used to determine the potential genetic diversity among strains. Clustering of PCR MP fingerprinting data matched with rep‐PCR fingerprinting data. The generated distribution tree showed that Tunisian isolates were closely related to the citrus reference strain LMG5496. In contrast, EC112, isolated from citrus, and the almond isolate EC122 were distantly related to the type strain LMG1247 T isolated from lilac. Such studies have not been reported until now for P. syringae from citrus.